Application of life cycle carbon assessment for a sustainable building design: a case study in the UK. Issue 4 (16th March 2021) - Brooks, Maria; Abdellatif, Mawada; Alkhaddar, Rafid
ABSTRACT: In the construction industry, a large amount of carbon dioxide is emitted, due to the embodied and operational carbon. RICS Guidance note shows the stages producing the most carbon dioxide is the operational stage and the second significant area is the production stage. Recent studies have investigated reducing the operational emissions, however there is limited research on the embodied carbon. To achieve climate targets by 2050, all operational emissions need to be phased out along with reductions in embodied carbon. This paper aims to analyze the carbon life cycle (LCA) of the case study building in the UK. Further implementing low carbon & clean technologies have been considered to reduce the embodied and operational carbon. Current state of the art carbon assessment is utilized incorporating methodologies such as 'Cradle to grave' from 'British standards' in conjunction with 'RICS Guidance note' and 'RICS Professional statement.' To measure the embodied and operational carbon using the 'cradle to grave' process, requires selecting a case study building and collecting related input data to process calculations such as construction materials and energy consumption. Results conclude that the operational stage is the largest CO₂ contributor of the whole lifecycle, therefore PV Solar panels were chosen to reduce CO₂ emissions. The product stage was the second most significant CO₂ contributor therefore low carbon strategies, such as use of recycled steel, light weight brick, and SCM's for mortar and concrete, were selected. Re-calculation of the embodied and operational carbon of the building after implementing the low carbon strategies and clean technology comparing to initial results show reductions in CO₂ emissions by 22% creating a low carbon building. Therefore, this paper brings awareness and guidance globally to clients, building designers, and the government to design sustainably using suitable low carbon solutions in all construction projects, leading to a low carbon future.